2022
DOI: 10.1021/jacs.2c07402
|View full text |Cite
|
Sign up to set email alerts
|

A Planar Nickelaspiropentane Complex with Magnesium-Based Metalloligands: Synthesis, Structure, and Synergistic Dihydrogen Activation

Abstract: The nature of transition-metal–olefin bonding has been explained by the Dewar–Chatt–Duncanson model within a continuum of two extremes, namely, a π-complex and a metallacyclopropane. The textbook rule suggests that a low-spin late-transition-metal–ethylene complex more likely forms a π-complex rather than a metallacyclopropane. Herein, we report a low-spin late-transition-metal–bis-ethylene complex forming an unprecedented planar metalla-bis-cyclopropane structure with magnesium-based metalloligands. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 90 publications
(51 reference statements)
1
34
0
Order By: Relevance
“…[33,34] H2 addition to a Ni complex related to 1 has been calculated to occur by a sbond metathesis pathway. [21] Despite these precedents, NBO analysis of key intermediates is consistent with the assignment as a ligand-assisted oxidative addition. Throughout the pathway the NPA charge on Pd becomes more positive (Int-1 = -0.37; Int-2 = -0.17; TS-1 = -0.16; Int-3 = -0.07; TS-2 = -0.05) suggestive of an increase in formal oxidation state of the transition metal on addition of H2.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…[33,34] H2 addition to a Ni complex related to 1 has been calculated to occur by a sbond metathesis pathway. [21] Despite these precedents, NBO analysis of key intermediates is consistent with the assignment as a ligand-assisted oxidative addition. Throughout the pathway the NPA charge on Pd becomes more positive (Int-1 = -0.37; Int-2 = -0.17; TS-1 = -0.16; Int-3 = -0.07; TS-2 = -0.05) suggestive of an increase in formal oxidation state of the transition metal on addition of H2.…”
Section: Resultsmentioning
confidence: 66%
“…[24,25] A closely related species Ni-Mg has very recently been reported by Xu and coworkers. [21] Scheme 2. Synthesis of tetrahydride complexes Pt-Mg•TMEDA and Pt-Zn Both Pt-Mg•TMEDA and Pt-Zn could be isolated as crystalline solids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Welldefined heterometallic hydrides have recently been reported, including recent examples featuring Ni-Mg and Ni-Zn bridged hydrides, yet their utilization in catalysis is in their infancy. [12][13][14] Various transition metal complexes are known to facilitate hydroboration of N-heterocycles, such as Rh, 15 Ru, 16 Fe, 17 and a recent example by the Findlater group featuring Ni. 18 In addition, complexes bearing redox-inactive metals such as La, Mg, and Zn as well as phospholenes are known to facilitate hydroboration of heterocycles.…”
mentioning
confidence: 99%
“…[26,27] A closely related species Ni-Mg has very recently been reported by Xu and co-workers. [21] Both Pt-Mg•TMEDA and Pt-Zn could be isolated as crystalline solids. X-ray diffraction studies confirmed that the coordination geometry at the transition metal is square planar (Figure 1).…”
mentioning
confidence: 99%